2007
DOI: 10.1111/j.1939-1676.2007.tb03023.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenocorticotropin, Cortisol, and Adrenocorticotropin/ Cortisol Ratios in Septic and Normal‐Term Foals

Abstract: Septic foals had higher hormone concentrations as compared to normal foals, which is an expected endocrine response to critical illness. The increased ACTH/cortisol ratio in nonsurviving septic foals in comparison to surviving septic foals could indicate hypothalamic-pituitary-adrenal axis dysfunction at the level of the adrenal gland in critically ill septic foals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 25 publications
7
75
2
Order By: Relevance
“…Baseline cortisol concentrations and expected ACTH stimulation test results have been published for 0.1 μg/kg, 10 μg/foal, 100 μg/foal, and 250 μg/foal doses of cosyntropin for healthy foals at various ages. Septic foals have been found to have significantly higher concentrations of endogenous ACTH and baseline cortisol than normal foals, as would be expected during physiologic stress of illness. However, Wong et al reported no differences in these endogenous hormone concentrations when comparing septic and nonseptic sick, or when comparing sick and healthy foals .…”
Section: Diagnosismentioning
confidence: 75%
See 1 more Smart Citation
“…Baseline cortisol concentrations and expected ACTH stimulation test results have been published for 0.1 μg/kg, 10 μg/foal, 100 μg/foal, and 250 μg/foal doses of cosyntropin for healthy foals at various ages. Septic foals have been found to have significantly higher concentrations of endogenous ACTH and baseline cortisol than normal foals, as would be expected during physiologic stress of illness. However, Wong et al reported no differences in these endogenous hormone concentrations when comparing septic and nonseptic sick, or when comparing sick and healthy foals .…”
Section: Diagnosismentioning
confidence: 75%
“…However, Wong et al reported no differences in these endogenous hormone concentrations when comparing septic and nonseptic sick, or when comparing sick and healthy foals . Endogenous ACTH concentrations and ACTH‐cortisol ratios appear to be significantly higher in nonsurviving septic foals than in survivors, suggesting their adrenal glands may be inadequately responsive to ACTH. Dembek et al reported that septic nonsurviving foals had lower baseline cortisol concentrations than survivors, while Armengou et al found that critically ill nonsurviving foals (both septic and nonseptic) had higher admission cortisol concentrations than survivors .…”
Section: Diagnosismentioning
confidence: 99%
“…Survival of premature and dysmature foals is influenced by the degree of maturity of several key endocrine systems . In particular, immaturity of the hypothalamic‐pituitary‐adrenal axis is associated with impaired stress responses and increased mortality in the face of sepsis . Hypoglycaemia and hyperglycaemia can both occur in critically ill foals , as in human neonates .…”
Section: Alterations In Insulin Metabolism In the Foalmentioning
confidence: 99%
“…The reagents are specifically designed for use with the Immulite 1000 ® automated analyzer. This assay is used regularly for clinical diagnostic quantification of ACTH in unextracted equine (Perkins et al, 2002) and canine (Scott-Moncrieff et al, 2003;Galac et al, 2005) plasma samples by the AHDC Endocrinology Laboratory and has been used in research applications for other species primarily with equine samples (Donaldson et al, 2005;Gold et al, 2007). The analytical sensitivity of the assay is 9 pg/mL, and the calibration range is up to 1,250 pg/mL.…”
Section: Acth Analysismentioning
confidence: 98%